Implementasi Pendidikan Akhlak Ta’awun Antar Anak Tunanetra Dan Tunagrahita - Eli Tina Wati; Nurul Iman; Azid Syukroni (AL-ASASIYYA: Journal Of Basic Education, 2021)
The purpose of this study was to determine the implementation of ta'awun moral education among blind and mentally retarded children at the Integrated Blind Orphanage 'Aisyiyah Ponorogo. This study used a qualitative approach, and the data was collected using interviews, observation and documentation, all of which were used to answer questions about the implementation of ta'awun moral education among blind and mentally retarded children. The results of this study indicate that the implementation of ta'awun moral education is carried out through learning activities. One of these learning activities is to teach religious materials such as aqidah morals, fiqh and several other religious lessons. Meanwhile, the educational method used is exemplary, habituation, advice and by paying attention to foster children. As for the supporting factors in the implementation of this implementation, namely, the existence of an organizational structure for the care division which will later control the activities of foster children in the orphanage, then the social environment and infrastructure that support learning activities. While the result of the moral education is that they are still young, but they grow into extraordinary children with their limitations. The spirit of helping him is used to it.